Penyusunan Program Sekolah Literasi SD/MI Di Kedungbanteng Kecamatan Tanggulangin Sidoarjo - Wulandari, Fitria; Wulandari, Fitria Eka; Febryanti, Siti Aulia; Dewi, Elisa Prezilia (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2021)
This Community Service activity aims to (1) provide insights and knowledge of elementary / MI teachers in Kedungbanteng Tanggulangin the importance of the school literacy movement program to increase student literacy in schools, (2) SD / MI in Kedungbanteng Tanggulangin in order to have a literacy school program, (3) increase the mastery of teachers in the use of facilities and infrastructure as a support in the implementation of school literacy programs. The method used to solve these problems is through training and mentoring activities. From community service activities titled training and mentoring for the preparation of elementary / MI literacy school programs in Kedungbanteng Tanggulangin Sidoarjo shows that the activities are going well and smoothly. The achieved outcome is that the school has a literacy school program. The results of training and mentoring on the material presented can add insight and knowledge about the literacy school program as much as 72.2% strongly agree and 27.8% agree. The material presented is able to guide teachers to be able to compile a literacy school program of 55.6% strongly agree and 44.4% agree. the assistance provided can assist teachers in implementing the literacy school program that has been prepared as many as 66.7% stated agree and 33.3% stated strongly agree.